Mycorrhizal Response of Potato Plants to Homokaryotic Versus Dikaryotic Arbuscular Mycorrhizal Fungi - Terry, Victoria Catherine (Université d'Ottawa / University of Ottawa, 2022)
Arbuscular mycorrhizal fungi (AMF) are obligate plant symbionts that colonize the roots of the majority of vascular land plants. These fungi have a unique nuclear organization, in which thousands of nuclei co-exist among an unsegmented fungal body. In individual strains these nuclei can all be genetically similar (homokaryotic) or be derived from two distinct parents (dikaryotic). In other fungal groups the presence of two distinct nuclei in one cell (fungal dikaryons) can change their fitness, function, and symbiotic relationship; begging the question, what impact does the presence of two parental genotypes have on the arbuscular mycorrhizal symbiosis? I am investigating this by measuring the mycorrhizal response (MR) of potato cultivars with different degrees of domestication using representative AMF homokaryons (4) and AMF dikaryons (4). I found that the genetic organization (dikaryotic vs homokaryotic) and domestication status of the host (modern vs old) are both significant factors in the mycorrhizal response of host plants. Specifically, biomass is significantly greater when inoculated with homokaryotic AMF compared to dikaryotic AMF. Dikaryotic strains have low arbuscule colonization in modern cultivars and higher in old, although there are not significant differences in other fungal responses between homokaryotic and dikaryotic AMF. Furthermore, nutrient uptake (N and P) is greater in old cultivars than modern cultivars, although the root:shoot ratio is lower in old cultivars. Analyses of single spores using digital droplet PCR (ddPCR) confirm that nucleotype ratio of dikaryotic spores shifts depending on the host identity. This research provides novel insights into the role of AMF genetic organization in the mycorrhizal symbiosis in greenhouse conditions. In particular, this work shows that the presence of two distinct nucleotypes results in the fungi being more readily adaptable to the host leading to a more stable MR and a potentially selfish strategy, when in symbiosis with potato cultivars.
Keywords: mycorrhizal response; AMF dikaryons; mycorrhiza; domestication; potato